Systems Biology of Free Radicals and Antioxidants - Laher, Ismail (Springer Berlin Heidelberg : Imprint: Springer, 2014)
The focus of this collection of illustrated reviews is to discuss the systems biology of free radicals and anti-oxidants. Free radical induced cellular damage in a variety of tissues and organs is reviewed, with detailed discussion of molecular and cellular mechanisms. The collection is aimed at those new to the field, as well as clinicians and scientists with long standing interests in free radical biology. A feature of this collection is that the material also brings insights into various diseases where free radicals are thought to play a role. There is extensive discussion of the success and limitations of the use of antioxidants in several clinical settings.